Promising regions for detecting the overturning circulation in Atlantic 231Pa/230Th: a model-data comparison - Scheen, Jeemijn; Lippold, Jörg; Pöppelmeier, Frerk; Süfke, Finn; Stocker, Thomas (Paleoceanography and paleoclimatology, 2025)
The Atlantic Meridional Overturning Circulation (AMOC) is a critical component of the climate system, strongly influencing the climate via ocean heat transport. The AMOC is thought to have had different characteristics during glacial periods and is expected to change under anthropogenic climate forcing. To reconstruct past AMOC strength, the 231Pa/230Th (protactinium-231 to thorium-230) ratio measured in marine sediments serves as an often used proxy. However, this ratio reflects not only circulation changes, but also effects from biological particle export and benthic nepheloid layers. Therefore, it remains an open question which regions exhibit a reliable AMOC signal in their sedimentary 231Pa/230Th. We utilize the Bern3D model and a compilation of sediment 231Pa/230Th records, including records from 11 new core locations. This study suggests that equatorial West Atlantic 231Pa/230Th is as suitable as the Bermuda Rise region to detect AMOC changes. The 231Pa/230Th response to AMOC changes observed in part of the northern North Atlantic (which is opposite to regions further south) is caused mainly by AMOC-induced changes in particle production. Cores in this region are promising to reconstruct AMOC strength, despite exhibiting an AMOC-to-231Pa/230Th relationship opposite from usual and high opal levels. Additional cores in the North Atlantic at 40°-60°N between 1 and 2 km depth are desirable for the application of 231Pa/230Th. Our results suggest a new focus of 231Pa/230Th reconstructions on the equatorial West Atlantic and the northern North Atlantic, which appear to be best suited to quantify past AMOC strength.
Online verfügbar: 06. März 2025
Im Titel erscheinen 231 und 230 hochgestellt
Gesehen am 25.08.2025